Optimasi Parsial Isolat Termofilik M5-24 dalam Produksi Protease - Aghni Aznia; Anthoni Agustien; Nasril Nasir (Jurnal Biologi Universitas Andalas, 2014)
Research about partial optimization of thermophilic bacteria isolate M5-24 on protease production was conducted from May 2013 to December 2013 in Laboratory of Microbiology, Biology Department, Andalas University, Padang. Purpose of the research was to find out optimum condition of protease production by isolate M5-24. This study consisted of three steps. Step 1: Investigating the effect of temperature and pH used completely randomized design in factorial with two replications.The first factor was temperature (450C, 500C, 550C, 600C), the second factor was pH (7, 8, 9, 10). Step 2: Investigating the effect of inoculum doses and inducers used completely randomized design in factorial with three replications. The first factor was inoculum doses (1%, 5%, 10%) and the second factor was inducer (yeast extract 0,5%; pepton 0,1%;  kasein 1%; meat extract 0,5%). While Step 3: Investigating the effect of agitation (125 rpm, 150 rpm, 175 rpm, 200 rpm) used completely randomized design with six replications. The result showed that the best duration of growing was at 18th hours after incubation, the highest enzyme activity was at temperature 500 C;  medium’s pH at 8; the best of inoculum dose was at 5%; the best  inducer was casein 1% and optimum agitation was at 175 rpm. Extrinsic optimization can increase protease production of  thermophilic isolate M5-24 up to 1.7 times.Keywords : Optimization, Protease,  thermophilic, bacteria